John Tyler Bonner: Remembering a scientific pioneer. Issue 8 (19th November 2019) - Brigandt, Ingo; Katz, Laura A.; Nanjundiah, Vidyanand; Gilbert, Scott F.; Grant, Peter R.; Grant, B. Rosemary; Love, Alan C.; Newman, Stuart A.; West‐Eberhard, Mary J.
Abstract: Throughout his life, John Tyler Bonner contributed to major transformations in the fields of developmental and evolutionary biology. He pondered the evolution of complexity and the significance of randomness in evolution, and was instrumental in the formation of evolutionary developmental biology. His contributions were vast, ranging from highly technical scientific articles to numerous books written for a broad audience. This historical vignette gathers reflections by several prominent researchers on the greatness of John Bonner and the implications of his work